Characterization Study of Four Candidate Technologies for Nuclear Material Quantification in Fuel Debris at Fukushima Daiichi Nuclear Power Station. (December 2017) - Nagatani, Taketeru; Komeda, Masao; Shiba, Tomooki; Nauchi, Yasushi; Maeda, Makoto; Sagara, Hiroshi; Kosuge, Yoshihiro; Kureta, Masatoshi; Tomikawa, Hirofumi; Okumura, Keisuke; Heinberg, Cynthia; Hori, Keiichiro
Abstract: This paper provides an interim report for characterization study of four candidate technologies for nuclear material quantification in fuel debris at Fukushima Daiichi Nuclear Power Station (1F). The severe loss-of-coolant accidents of 1F produced fuel debris in the reactor cores of Units 1-3. Because the fuel debris would contain unknown amounts of minor actinides, fission products and neutron absorbers and the mixing rate of them would vary significantly, accurate quantification of nuclear material in fuel debris would be difficult by applying a single measurement technology. Therefore, we consider that an integrated measurement system that combines several measurement technologies would be required to complement the weakness of each technology. For consideration of an integrated measurement system, we conducted a characterization study for each technology. In order to compare the results of applicability evaluation of each technology, common set of simulation models for fuel debris and canister were developed. These models were used for the applicability evaluation of each technology. Then, the comparative evaluation of the result of applicability evaluation among four technologies was conducted.